2020
DOI: 10.36367/ntqr.3.2020.318-330
|View full text |Cite
|
Sign up to set email alerts
|

Valoración De Los Factores Que Condicionan La Adquisición De Hábitos Alimentarios Saludables en Personas Con Trastorno Mental Grave (Tmg): Aproximación Cualitativa Desde Una Perspectiva en Primera Persona Y De Los Profesionales

Abstract: Resumen. Introducción: La adopción de dietas de baja calidad nutricional se relaciona con la aparición de alteraciones metabólicas, factor que contribuye a la elevada tasa de comorbilidades entre las personas con TMG. Conocer los factores condicionantes permite desarrollar programas de educación alimentaria adecuados a las necesidades de la persona; Objetivos: Explorar los factores que condicionan la adopción y mantenimiento de los hábitos alimentarios, e identificar las estrategias más eficientes para el camb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Other authors have identified a relationship between gender, age, and BMI and the intake of F&V [ 12 ]. In a qualitative study that addressed the factors that condition the acquisition of healthy eating habits conducted with people with SMDs and care professionals, both groups pointed to the complexity of maintaining healthy eating habits when professional support is no longer in place, often leading to an abandonment of acquired behaviour [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have identified a relationship between gender, age, and BMI and the intake of F&V [ 12 ]. In a qualitative study that addressed the factors that condition the acquisition of healthy eating habits conducted with people with SMDs and care professionals, both groups pointed to the complexity of maintaining healthy eating habits when professional support is no longer in place, often leading to an abandonment of acquired behaviour [ 34 ].…”
Section: Discussionmentioning
confidence: 99%